Family succession and firm performance among Malaysian companies - Amran, Noor Afza (Centre for Promoting Ideas, 2010)
Family succession is one of the prevalent topics discussed in family management. However, there is lack of research on the issue of succession in Malaysia despite the f act that about 70% of listed companies in Malaysia are owned by family related business.Thus, this study aims to examine the relationship between family succession attributes and firm performance.This study adopted balanced panel data analysis for 975 companies listed on Bursa Malaysia for the year 2003 to 2007. The findings indicate that some of the family succession attributes do influence firm performance.Family ownership was found to be positively related with firm performance.Families are motivated to work efficiently when more shares were in their hands. Furthermore, the results reveal that successors-managed firms have better firm performance than founder-managed firms. The findings provide evidenced that Malaysian family firms do plan for their success ions.More importantly, it opens up the possibilities for further study of family succession, both in Malaysia and on global basis.